2019
DOI: 10.1016/j.ajoc.2019.100474
|View full text |Cite
|
Sign up to set email alerts
|

Peritomy-sparing scleral buckle

Abstract: Abstrac Purpose To introduce a modified technique for encircling circumferential scleral buckling without peritomy thorough a small conjunctival opening for the repair of uncomplicated rhegmatogenous retinal detachment (RD). Methods This technique was performed in 10 eyes of 10 patients with primary rhegmatogenous RD who underwent encircling circumferential scleral buckling without peritomy. Transconjunctival traction sutures were placed in four rectus musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Scleral belt loop tunnels are becoming increasingly popular for securing the encircling band to the sclera. [4][5][6][7] Spontaneous dehiscence of scleral loop tunnels is rare. Fukumoto et al 8 reported a patient who presented with mild foreign body sensation and visible silicone band under the conjunctiva one year after a combined pars plana vitrectomy and SB surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scleral belt loop tunnels are becoming increasingly popular for securing the encircling band to the sclera. [4][5][6][7] Spontaneous dehiscence of scleral loop tunnels is rare. Fukumoto et al 8 reported a patient who presented with mild foreign body sensation and visible silicone band under the conjunctiva one year after a combined pars plana vitrectomy and SB surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The method has recently gained popularity as more SB procedures are performed under microscopy, as a "sutureless" surgery, or using 3D visualization systems. [4][5][6][7] In this method, the encircling buckle material is anchored to sclera through a partial thickness circumferential scleral tunnel that is usually dissected using a crescent knife. Globe perforation through full-thickness None of the authors has any financial/conflicting interests to disclose.…”
mentioning
confidence: 99%